Perubahan Status Gizi Balita Dengan Akupresur Selama Pemberian Makanan Tambahan (PMT) Pemulihan Pada Balita - Enggar Anggraeni; Mirthasari Palupi; Risma Trisnagati (Poltekkes Kemenkes Mataram, 2020)
Background : Nutritional problems are still one of the problems faced by Indonesia. Malnutrition and micronutrient deficiencies are major nutritional problems facing Indonesia. Macro-nutrient deficiency occurs when the body lacks energy and protein, this is due to a gap between nutritional needs and nutrient intake so that it can cause a deficiency of micronutrients in the body which has an impact on malnutrition or malnutrition status. Inadequate nutrition is a condition of a lack of energy and protein intake, while malnutrition is a lack of energy and protein intake for a long period of time. Provision of Recovery Supplement (PMT Recovery) is a program aimed at overcoming the problem of malnutrition and malnutrition by improving nutritional status, fulfilling children's nutritional needs so that good nutritional status and condition are achieved according to the child's age. So that in this study the role of PMT is used in order to increase body weight and nutritional status of children. Objectives : The purpose of this study was to distinguish nutritional status during supplementation with supplementary food with acupressure. Methods : This research uses quantitative research type, with the research design used is Quasy Experiment with Pre and Post Test Control Group Design approach. The statistical test used was the Independent t-Test and Wilcoxon test. Results : The results of the study conducted on 3 - 16 July 2020 with a sample of 10 toddlers with acupressure, weight gain before and after PMT administration ranged from 0.2 to 0.4 kg, while the p value is 0.004 <0.05 then there are the difference between body weight before and after giving PMT. As for the Nutritional Status of the statistical test results obtained p value of 0.083 (> 0.05) which indicates that there is no difference between the nutritional status of children under five before and after giving PMT.